The impacts of graphene dosage on the friction and wear performance of a graphene-reinforced silicone rubber nano composite - Shinde, Avinash; Siva, I.; Munde, Yashwant; Sankar, I.; Sultan, Mohamed Thariq Hameed; Mustapha, Faizal; Shahar, Farah Syazwani; Najeeb, Muhammad Imran (Elsevier, 2022)
Lightweight elastomer nanocomposites have several uses in the automotive and aerospace industries. There ought to be no compromises in terms of efficiency, durability, or performance when it comes to new technological products. This results in the ongoing quest for innovative materials. This study contributes to the development of graphene-reinforced silicone rubber by evaluating its mechanical and tribological properties. The two-roll mill mixing process, followed by the moulding step, is utilised in commercial nanocomposites preparation. As a result, the man-made composite can be justified financially. The moulding process was carried out at 170 °C, and the final curing took place at 200 °C for 4 h. Testing is done using filler weight percentages of 0, 1, 3, 5, and 7% graphene to determine the optimal filler weight %. The mechanical performance of silicon rubber was enhanced by over 213% when the graphene weight percentage was increased. With increasing load, the coefficient of friction decreases, with the lowest value found at 3% graphene by weight. The coefficient of friction and the specific wear rate were discovered to vary with sliding speed.